Growing up Ziglar a daughter's broken journey from heartache to hope - Norman, Julie Ziglar (New York, N.Y. : Guideposts, 2012)
With God, it's never to late to be your best you. As the daughter of Zig Ziglar, the motivator's motivator, Julie knew that she needed to be positive-- but spent much of her life as the poster child for "doing life wrong." She tells you how she discovered the path from heartache to redemption, and helps you on your own journey of transformation in order to experience God's grace and forgiveness more profoundly.
Julie Ziglar Norman often says that her dad is the king of "doing life right" and that she is the poster child for "doing life wrong." For over a quarter of a century, she lived every day with regret, shame, guilt, and depression. But she was the daughter of the movtivator's motivator, Zig Ziglar, and knew that she needed to be positive. So, she gathered up all of her negative self-talk and squashed it deep down inside where it couldn't ruin the bright and practiced smile she presented to the world. "People might assume Zig Ziglar's daughter would automatically grow up to have a positive attitude," Julie says. "For a large portion of my life, I was just positive I was miserable!" Her powerful and heartwarming story will move readers to laughter and tears. Above all, it will renew their faith in God's power to redeem all the wrong choices and bring them full circle to hope and healing. Julie urges readers not to settle for okay when God has true joy waiting for them. She shares...
Adorable, willing, and obedient -- I never wanted this! -- Just be -- He loves me, he loves me not -- Different choices -- The real issues of choice making -- The single-parent years -- Progress, not perfection -- Reality-based living -- Losing Suzan -- Alvord, Texas! -- Pivotal life point -- Grow up and be your best -- Attitude and choices -- The next right thing.
Description based on print version record.
Keywords: Norman, Julie Ziglar; Single mothers -- Biography; Christian biography; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christian Life / General; Electronic books